Joseph Schacht dalam Pandangan Sarjana Hadis Indonesia - Benny Afwadzi (IAIN Bengkulu, 2023)
This article examines how the existence of Joseph Schacht, the main character in the study of hadith in the West, in the discourse of thought of Indonesian hadith scholars. Although he is a Western scholar living in Europe, his influence of thought also reached Indonesia through lectures and discussions about orientalist hadith, both inside and outside the classroom. This article aims to map out the response of Indonesian hadith scholars to Schacht's ideas. Using a qualitative approach and the type of library research, this article concludes that Schacht does have a fairly strong influence in Indonesia; most of the writings that discuss the study of hadith among orientalists, with any character, do not forget to present Schacht as an important figure. Furthermore, hadith scholars are divided into three camps in responding to Schacht's ideas, namely the contra, the pros, and the middle. The arguments that are carried out are also different, ranging from academic to ideological ones. The main current that appears in the thought of Indonesian hadith scholars is against Schacht, which is motivated by subjectivity as a Muslim, in addition to Schacht's thinking which is problematic and has many problems.